Neural and oligodendrocyte progenitor cells: transferrin effects on cell proliferation - Silvestroff, Lucas (2013)
NSC (neural stem cells)/NPC (neural progenitor cells) are multipotent and self-renew throughout adulthood in the SVZ (subventricular zone) of the mammalian CNS (central nervous system). These cells are considered interesting targets for CNS neurodegenerative disorder cell therapies, and understanding their behaviour in vitro is crucial if they are to be cultured prior to transplantation. We cultured the SVZ tissue belonging to newborn rats under the form of NS (neurospheres) to evaluate the effects of Tf (transferrin) on cell proliferation. The NS were heterogeneous in terms of the NSC/NPC markers GFAP (glial fibrillary acidic protein), Nestin and Sox2 and the OL (oligodendrocyte) progenitor markers NG2 (nerve/glia antigen 2) and PDGFRα (platelet-derived growth factor receptor α). The results of this study indicate that aTf (apoTransferrin) is able to increase cell proliferation of SVZ-derived cells in vitro, and that these effects were mediated at least in part by the TfRc1 (Tf receptor 1). Since OPCs (oligodendrocyte progenitor cells) represent a significant proportion of the proliferating cells in the SVZ-derived primary cultures, we used the immature OL cell line N20.1 to show that Tf was able to augment the proliferation rate of OPC, either by adding aTf to the culture medium or by overexpressing rat Tf in situ. The culture medium supplemented with ferric iron, together with aTf, increased the DNA content, while ferrous iron did not. The present work provides data that could have a potential application in human cell replacement therapies for neurodegenerative disease and/or CNS injury that require the use of in vitro amplified NPCs.